Meningkatkan Kecerdasan Linguistik Anak Usia Dini melalui Kegiatan Bermain Peran - Khairiah, Dina; Putri, Anisa; Arifin, Darul; Asrima, Nur; Manalu, Ali Wardhana (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study aims to determine the effect in depth and examine the relationship between role playing and the development of linguistic intelligence of early childhood in RA Al-Huda. This research was conducted using a descriptive method using a qualitative approach. The results of this study indicate: 1) role playing is a method that is widely used and is considered capable of developing children's linguistic intelligence because it will stimulate empathy and understand and appreciate  whatever professions do other people, 2) teachers have a big role in assisting children to help shape children's character through role playing activities, and 3) linguistic intelligence can develop better if the right methods are continuously applied. This study concludes that role playing can affect the linguistic intelligence of early childhood.